Low-modulus silane modified polyether sealant as well as preparation method and application thereof
A low modulus silane-modified polyether sealant using foamed ceramic tailings as fillers addresses cost issues, enhancing flexibility and suitability for prefabricated buildings while promoting environmental sustainability.
Patent Information
- Application Number
- CN202411329401.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
AI Technical Summary
The high cost of silane-modified polyether sealants restricts their application in prefabricated building wall sealing, despite their excellent mechanical properties and weather resistance, necessitating a low modulus variant with reduced costs and improved reinforcement and toughness.
A low modulus silane-modified polyether sealant is developed using foamed ceramic tailings as fillers, combined with silane-modified polyether polymer, plasticizer, coupling agent, and catalyst, through a vacuum-reacted preparation method to enhance flexibility and reduce costs.
The sealant achieves good elongation at break, flexibility, and cost-effectiveness by recycling industrial waste, promoting environmental protection and suitability for prefabricated buildings.
Smart Images

Figure CN119193076A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealants, and in particular to a low-modulus silane-modified polyether sealant and a preparation method and application thereof. Background Art
[0002] With the advocacy of energy conservation and environmental protection, the development of green buildings, the development trend of prefabricated buildings is unstoppable. The horizontal and vertical joints of prefabricated buildings require sealants for bonding and sealing, so the demand for sealants for prefabricated exterior wall joints and board joints will also show an upward trend.
[0003] Prefabricated lightweight interior wall panels and partitions in prefabricated buildings have high requirements for sealant displacement resistance, elastic recovery rate and weather resistance. Compared with other types of sealants, silane-modified polyether sealants show advantages in excellent mechanical properties, coating properties and stain resistance. Therefore, it is gradually becoming one of the main trends in the development of new generation sealants at home and abroad.
[0004] However, due to its high cost, its application in the field of prefabricated building wall sealing is seriously restricted. Therefore, the field urgently needs to develop a low modulus silane-modified polyether building sealant with low cost and good reinforcement and toughening effect, which can be widely used in the field of prefabricated building wall sealing.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a low modulus silane-modified polyether sealant and a preparation method and application thereof, so as to solve the above technical problems.
[0007] The present invention is achieved in that:
[0008] In a first aspect, an embodiment of the present invention provides a low modulus silane-modified polyether sealant. The low modulus silane-modified polyether sealant comprises the following raw materials in parts by weight:
[0009] 50-100 parts of silane-modified polyether polymer, 30-50 parts of plasticizer, 30-180 parts of filler, 1-4 parts of coupling agent, 1-2 parts of catalyst; the filler is foamed ceramic tailings.
[0010] In a second aspect, an embodiment of the present invention provides a method for preparing the low modulus silane-modified polyether sealant as described above, comprising the following steps:
[0011] Add silane-modified polyether polymer, plasticizer and filler into the equipment in proportion to react, the reaction temperature is 60-120°C, the reaction time is greater than 0.5h, the vacuum degree is ≥-0.09MPa, and a first mixture is obtained; the first mixture is cooled to 25-45°C, a coupling agent and a catalyst are added to react, the reaction time is ≥0.5h, the vacuum degree is ≥-0.09MPa, and the mixture is cooled to room temperature to obtain a low modulus silane-modified polyether sealant.
[0012] In a third aspect, an embodiment of the present invention provides an application of the low modulus silane-modified polyether sealant as described above or the low modulus silane-modified polyether sealant prepared by the preparation method as described above in the field of prefabricated buildings.
[0013] The present invention has the following beneficial effects:
[0014] The low modulus silane-modified polyether sealant provided in the embodiment of the present invention is based on the perspective of filler. Foamed ceramic tailings are added as fillers during the preparation process. By changing the performance of the filler, the purpose of reducing costs and strengthening and toughening is achieved. The preparation method is simple and easy to operate. The prepared low modulus silane-modified polyether sealant has good elongation at break and exhibits good flexibility. The present invention recycles foamed ceramic tailings, reduces costs and is beneficial to the development of environmental protection, and can be widely promoted in the field of prefabricated buildings. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0016] Figure 1 The physical appearance diagram of the spline of Embodiment 1-6;
[0017] Figure 2 It is the SEM test picture of Example 1-6;
[0018] Figure 3 Schematic diagram of tensile strength data of Examples 1-6;
[0019] Figure 4 Schematic diagram of tensile strength data of Examples 7-12;
[0020] Figure 5 It is a schematic diagram of the elongation at break data of Examples 1-6;
[0021] Figure 6 It is a schematic diagram of the elongation at break data of Examples 7-12;
[0022] Figure 7 It is a schematic diagram of the test data of the hardness of Examples 1-6;
[0023] Figure 8 Schematic diagram of the performance characterization test of Example 7 and Examples 15-18. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0025] In a first aspect, an embodiment of the present invention provides a low modulus silane-modified polyether sealant. The low modulus silane-modified polyether sealant comprises the following raw materials in parts by weight:
[0026] 50-100 parts of silane-modified polyether polymer, 30-50 parts of plasticizer, 30-180 parts of filler, 1-4 parts of coupling agent, 1-2 parts of catalyst; the filler is foamed ceramic.
[0027] It should be noted that the relative molecular mass of the silane-modified polyether polymer used in the present invention is 15000-30000, which belongs to a low modulus silane-modified polyether polymer. It has the following characteristics: good thixotropy and extrudability, wide applicable temperature range, easy construction and use; excellent bonding performance for most building materials such as stone, aluminum, ceramics, precast concrete components (FC boards), cement fiber boards, etc., and no pollution to porous substances; it does not contain solvents, PVC, or isocyanates, so it is non-toxic, odorless, pollution-free, and has a fast curing speed, meeting environmental protection requirements.
[0028] In an optional embodiment of the present invention, the silane-modified polyether polymer is selected from any one of trimethoxysiloxane-terminated polyether and dimethoxysiloxane-terminated polyether;
[0029] It should be noted that silane-modified polyether polymer is a new type of polymer material that combines the properties of silane and polyether and has excellent performance. This polymer material uses conventional polyether polyurethane modified by siloxane as the main chain to form a new type of polyurethane polymer. It not only has better water resistance and weather resistance, but also shows good adhesion to difficult-to-bond surfaces such as glass and plastic. Its main molecular chain is a macromolecular polyether terminated with methoxysilane, which forms a three-dimensional spatial network structure with Si-O-Si as the skeleton after curing. This structure gives the material good weather resistance and good adhesion, and has broad application prospects in the fields of construction, sealants, etc.
[0030] Furthermore, the silane-modified polyether polymer is a trimethoxysiloxane-terminated polyether.
[0031] In an optional embodiment of the present invention, the foamed ceramic tailings account for 80-180 parts by weight.
[0032] It should be noted that foamed ceramic tailings are waste produced during the industrial preparation of foamed ceramics. Recycling them as fillers for low-modulus silane-modified polyether sealants has great economic potential and can also save a lot of natural resources. The recycling of industrial solid waste not only reduces cost investment, but also helps protect the ecological environment and improve people's quality of life.
[0033] Specifically, the silica particles contained in the foamed ceramic tailings generate hydrogen bonds through the silanol groups on their surfaces, forming a silica aggregate network that limits the fluidity of the system, increases the viscosity, and plays a thickening role; under the action of shear force, the silica network is destroyed, causing the viscosity of the system to decrease, resulting in a thixotropic effect, which is convenient for construction. Once the shear force is eliminated, this network structure can be re-formed, effectively preventing the sealant from sagging during the curing process.
[0034] The chemical composition of the foamed ceramic tailings used in the embodiment of the present invention is SiO 2 : 54.35%-68.96%, Al 2 O 3 :8.45%-14.34%,Fe 2 O 3 : 0.2%-0.6%, TiO 2 :0.04%-0.2%, CaO: 5.04%-18.4%, MgO: 1.1%-3.1%, K 2 O: 0.5%-5.8%, Na 2 O: 3.5%-9%, BaO: 0.02%-3.01%, ZnO: 0.05%-8%, LOI: 0.2%-3%.
[0035] It should be noted that the specific composition of the foamed ceramic tailings is related to the production batch and the amount of raw materials used. In other embodiments of the present invention, the composition of the foamed ceramic tailings may vary with different production batches.
[0036] In an optional embodiment of the present invention, the plasticizer is selected from any one of polypropylene glycol (PPG1000, PPG2000, PPG3000), polybutylene glycol (PTMG), diethyl phthalate (DINP), dioctyl phthalate (DOP) and bisphenol A epoxy resin.
[0037] It should be noted that the addition of plasticizers can effectively reduce the surface hardness of polymers; change the structure of polymers to make them softer; reduce the processing temperature of polymers and improve their fluidity; when plasticizers melt with polymers, their small molecules are inserted into the polymer molecular chains, allowing the polymer to transform from a glassy state to a rubbery state at a lower temperature, thereby reducing the glass transition temperature of the polymer.
[0038] Excessive use of plasticizers will destroy the network structure of the polymer, resulting in a decrease in the physical and mechanical properties of the material, including a decrease in strength, hardness and heat resistance; secondly, the product will have poor dimensional stability and a sticky surface. If too little plasticizer is added, the required flexibility and ductility may not be achieved.
[0039] In a preferred embodiment of the present invention, the plasticizer comprises polypropylene glycol.
[0040] In an optional embodiment of the present invention, the coupling agent is selected from any one of 3-(aminopropyl)trimethoxysilane (KH540), N-2-(aminoethyl)-3-(aminopropyl)trimethoxysilane (KH792), 3-(aminopropyl)triethoxysilane (KH550) and γ-glycidyloxypropyltrimethoxysilane (KH560).
[0041] It should be noted that coupling agent is a kind of organosilicon compound with special structure. The addition of coupling agent can increase the viscosity of the product and improve its viscosity. In its molecule, there are reactive groups that can combine with inorganic materials (such as glass, cement, metal, etc.) and reactive groups that can combine with organic materials (such as synthetic resin, etc.). Coupling agent is used as a surface modifier to improve the dispersibility and adhesion of plastics when it is filled with inorganic fillers. Coupling agent can not only increase the quality of plastics and reduce the cost of products, but also improve certain properties of plastic products.
[0042] If the amount of coupling agent added is too high, the product viscosity will be too high, affecting the use and dilution effect; secondly, it will cause the product color to change and affect the product quality and safety. If the amount of coupling agent used is too low, its effect cannot be maximized and the performance of the product will also decrease. In addition, the coupling agent needs to be mixed evenly with the other raw materials, otherwise the effect will decrease due to incomplete coating.
[0043] In a preferred embodiment of the present invention, the coupling agent includes N-2-(aminoethyl)-3-(aminopropyl)trimethoxysilane (KH792).
[0044] In an optional embodiment of the present invention, the catalyst is selected from any one of dibutyltin dilaurate and dibutyltin diacetate.
[0045] It should be noted that the addition of a catalyst can significantly shorten the curing time of the sealant by reducing the activation energy of the reaction, allowing the sealant to quickly reach a cured state at room temperature; secondly, the presence of a catalyst helps maintain good storage stability of the rubber. By selecting a suitable catalyst, such as dibutyltin dilaurate, it can be ensured that the sealant maintains its performance basically unchanged during storage, thereby ensuring the quality and durability of the product.
[0046] Using too much catalyst will lead to poor reaction selectivity, affecting product quality and output; secondly, it will increase the consumption of raw materials and raise costs; while using too little catalyst will affect the cross-linking reaction, resulting in insufficient cross-linking of the rubber molecules, poor mechanical properties of the rubber, and easy aging and cracking.
[0047] In a preferred embodiment of the present invention, the catalyst is dibutyltin dilaurate.
[0048] In a second aspect, an embodiment of the present invention provides a method for preparing the low modulus silane-modified polyether sealant as described above, comprising the following steps:
[0049] Add silane-modified polyether polymer, plasticizer and filler into the equipment in proportion to react, the reaction temperature is 60-120°C, the reaction time is greater than 0.5h, the vacuum degree is ≥-0.09MPa, and a first mixture is obtained; the first mixture is cooled to 25-45°C, a coupling agent and a catalyst are added to react, the reaction time is ≥0.5h, the vacuum degree is ≥-0.09MPa, and the mixture is cooled to room temperature to obtain a low modulus silane-modified polyether sealant.
[0050] In an optional embodiment of the present invention, before the filler is added to the equipment, the following steps are further included: adding foamed ceramic tailings, balls and water to a ball mill for ball milling in a mass ratio of (1.0-1.5): (1.6-2.7): (0.6-0.8), and drying the milled slurry to obtain the filler.
[0051] The present invention does not specifically limit the equipment for crushing the foamed ceramic. The crushing equipment used in the embodiment of the present invention is a ball mill, which can be reasonably adjusted according to actual needs. The present invention can grind the foamed ceramic tailings as fully as possible by setting a suitable ratio of material, balls and water, and achieve a better effect. The slurry after ball milling is sieved and then dried to obtain filler for standby use.
[0052] The mesh number of the filler can be reasonably adjusted according to actual needs. Taking into account the fluidity, tensile strength and elongation at break of the product, the mesh number of the filler used in the embodiment of the present invention is 300 meshes.
[0053] Reasonable setting of reaction temperature and vacuum environment are conducive to removing water from raw material components as much as possible. If there is water in the sealant, its performance and service life will be seriously affected, so the water content in the raw materials needs to be strictly controlled during the preparation stage.
[0054] Specifically, since silane-modified polyether adhesive is a moisture-curing product, it is very sensitive to moisture. The filler must be dried at high temperature before being added, and a vacuum reaction must be carried out during the preparation stage so that the remaining moisture content in the filler is less than 500ppm, reducing the impact on the later use of the sealant.
[0055] During the reaction, the materials need to be stirred continuously to make them evenly mixed. The speed is set to 400-800r / min.
[0056] The first mixture is continuously stirred during the cooling process, which is beneficial to accelerate the cooling of the material and to fully mix the material. When the temperature drops to 25-45°C, the coupling agent and catalyst are added to react, the reaction time is ≥0.5h, the vacuum degree is ≥-0.09MPa, and after the reaction is completed, the system is cooled to room temperature, the machine is stopped, and sampling is performed to obtain a low modulus silane-modified polyether sealant.
[0057] It should be noted that the coupling agent and catalyst should be added after the filler and the silane-modified polyether polymer are fully mixed. Since the foamed ceramic contains -SiOH, if the first mixture is not fully mixed before adding the coupling agent and catalyst, it will cause severe local condensation of the sealant and uneven cross-linking, affecting the overall performance of the product.
[0058] Specifically, the preparation method of the low modulus silane-modified polyether sealant provided by the present invention comprises the following steps:
[0059] The weighed foamed ceramic raw material, balls and water are added into a ball mill for pulverization, and the pulverized slurry is sieved and dried to obtain a filler;
[0060] The silane-modified polyether polymer, plasticizer and filler weighed in proportion are added to the glue-making equipment, and the stirring paddle is lowered to react for 10-30 minutes, and then the temperature is raised to 100° C., and vacuum is drawn to a vacuum degree of ≥-0.09 MPa, and stirring is continued for a reaction time of 1 hour at a rotation speed of 500 r / min to obtain a first mixed material;
[0061] Cool the first mixed material to 25-45°C, raise the stirring paddle, and scrape the materials on the stirring paddle and the inner wall of the glue making equipment into the glue making equipment;
[0062] Add coupling agent and catalyst to react for 10-30 minutes, evacuate, continue stirring, and the reaction time is 30-60 minutes. After the reaction is completed, cool to room temperature, stop, take samples, and obtain low modulus silane modified polyether sealant.
[0063] In a third aspect, an embodiment of the present invention provides an application of the low modulus silane-modified polyether sealant as described above or the low modulus silane-modified polyether sealant prepared by the preparation method as described above in the field of prefabricated buildings.
[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0065] Example 1
[0066] This embodiment provides a low modulus silane-modified polyether sealant, and the preparation steps thereof include the following:
[0067] The following materials were weighed according to the proportion: silane-modified polyether polymer (trimethoxysiloxane-terminated polyether, 100 parts), plasticizer (PPG3000, 40 parts) and filler 120 parts, added into a double planetary mixer for reaction, stirred for 20 minutes, heated to 100° C., vacuum degree was -0.09 MPa, and stirred for reaction for 1 hour to obtain a first mixture;
[0068] The first mixed material is cooled to 30°C, the stirring paddle is raised, and the materials on the stirring paddle and the inner wall of the mixer are scraped into the glue making equipment;
[0069] A coupling agent (1.5 parts of N-2-(aminoethyl)-3-(aminopropyl)trimethoxysilane (KH792)) and a catalyst (1 part of dibutyltin dilaurate) were added into a mixer to react with the first mixture. The mixture was stirred for 20 minutes at a vacuum degree of -0.09 MPa. The stirring reaction was continued for 30 minutes. After the reaction was completed, the mixture was cooled to room temperature, the machine was stopped, and a sample was taken to obtain a low modulus silane-modified polyether sealant.
[0070] Embodiment 2-6
[0071] Example 2-6 provides a low modulus silane-modified polyether sealant, which differs from Example 1 only in that:
[0072] The amount of filler used is different: the amount of filler used in Example 2 is 80 parts, the amount of filler used in Example 3 is 100 parts, the amount of filler used in Example 4 is 140 parts, the amount of filler used in Example 5 is 160 parts, and the amount of filler used in Example 6 is 180 parts.
[0073] Example 7
[0074] This embodiment provides a low modulus silane-modified polyether sealant, and the preparation steps thereof include the following:
[0075] The following materials were weighed according to the proportion: silane-modified polyether polymer (trimethoxysiloxane-terminated polyether, 100 parts), plasticizer (PPG3000, 50 parts) and filler 100 parts, added into a double planetary mixer, stirred for reaction for 20 minutes, heated to 100° C., evacuated to -0.09 MPa, and continued to stir for reaction for 1 hour to obtain a first mixed material;
[0076] The first mixed material is cooled to 30°C, the stirring paddle is raised, and the materials on the stirring paddle and the inner wall of the mixer are scraped into the glue making equipment;
[0077] A coupling agent (N-2-(aminoethyl)-3-(aminopropyl)trimethoxysilane (KH792, 2.5 parts) and a catalyst (dibutyltin dilaurate, 1.5 parts) were added into a blender, mixed with the first mixture, stirred for reaction for 20 minutes, vacuumed, and stirred for reaction for 30 minutes. After the reaction was completed, the mixture was cooled to room temperature, stopped, and sampled to obtain a low modulus silane-modified polyether sealant.
[0078] Examples 8-12
[0079] Examples 8-12 provide a low modulus silane-modified polyether sealant, which differs from Example 7 only in that:
[0080] The amount of coupling agent used is different: the amount of coupling agent used in Example 8 is 0 parts, the amount of coupling agent used in Example 9 is 1.0 parts, the amount of coupling agent used in Example 10 is 1.5 parts, the amount of coupling agent used in Example 11 is 2.0 parts, and the amount of coupling agent used in Example 12 is 3.0 parts.
[0081] Examples 13-14
[0082] Embodiment 13-14 provides a low modulus silane-modified polyether sealant, which differs from Embodiment 7 only in that:
[0083] The types of coupling agents are different: the coupling agent of Example 13 is γ-glycidyloxypropyltrimethoxysilane (KH560), and the coupling agent of Example 14 is 3-(aminopropyl)triethoxysilane (KH550).
[0084] Examples 15-18
[0085] Examples 15-18 provide a low modulus silane-modified polyether sealant, which differs from Example 7 only in that:
[0086] The types of plasticizers are different: the plasticizer of Example 15 is polypropylene glycol (PPG1000), the plasticizer of Example 16 is polypropylene glycol (PPG2000), the plasticizer of Example 17 is diethyl phthalate (DINP), and the plasticizer of Example 18 is dioctyl phthalate (DOP).
[0087] Examples 19-20
[0088] Examples 19-20 provide a low modulus silane-modified polyether sealant, which differs from Example 7 only in that:
[0089] The amount of catalyst used is different: the amount of catalyst used in Examples 19-20 is 1.0 parts, and the amount of catalyst used in Example 20 is 2.0 parts.
[0090] Embodiment 21
[0091] Example 21 provides a low modulus silane-modified polyether sealant, which differs from Example 7 only in that:
[0092] The types of catalysts are different. The catalyst used in this embodiment is 1.5 parts of dibutyltin diacetate.
[0093] Examples 22-23
[0094] Embodiment 22-23 provides a low modulus silane-modified polyether sealant, which differs from Embodiment 21 only in that:
[0095] The amount of catalyst used is different: the amount of catalyst used in Example 22 is 1.0 parts, and the amount of catalyst used in Example 23 is 2.0 parts.
[0096] Test Example 1
[0097] In this test example, the low modulus silane-modified polyether sealant prepared in Examples 1-6 was made into actual specimens, and photographs of their appearance were taken. The specific preparation method is as follows: The specimens are prepared according to the "dumbbell" type test specimen in GB / T528-2009 "Vulcanized Rubber or Thermoplastic Rubber-Determination of Tensile Stress-Strain Properties", and its specifications are 11.5×6×2mm and the thickness is 2mm. The specific preparation method is to fill the polytetrafluoroethylene mold with the sealant, scrape the surface of the mold flat, cure it under standard test conditions for 28 days, and then take out the sample. The appearance of the actual specimens of Examples 1-6 is shown in detail. Figure 1 (Filler dosage: a-80 parts, b-100 parts, c-120 parts, d-140 parts, e-160 parts, f-180 parts).
[0098] from Figure 1 It can be concluded that as the filler increases, the spline becomes slightly darker in color, and the color comes from the filler.
[0099] Test Example 2
[0100] In this test example, the low modulus silane-modified polyether sealant prepared in Examples 1-6 was subjected to SEM testing. The testing instrument was a field emission scanning electron microscope, specifically a TESCAN MIRA. The SEM test images of Examples 1-6 are shown in FIG. Figure 2 (Filler dosage: a-80 parts, b-100 parts, c-120 parts, d-140 parts, e-160 parts, f-180 parts).
[0101] from Figure 2 It can be concluded that from the SEM photos, no matter whether the filler content is low or high, there is a relatively fuzzy interface between the sealant matrix and the filler, which indicates that the filler and the silane-modified polyether sealant have good interfacial adhesion, thereby improving the interface morphology of the two.
[0102] Test Example 3
[0103] In this test example, the low modulus silane-modified polyether sealant prepared in Examples 1-12 was tested for tensile strength. The test standard was GB / T528-2009 "Vulcanized rubber or thermoplastic rubber - Determination of tensile stress-strain properties", the test instrument model was AI-7000S, and the tensile speed was 500mm / min. Among them, the tensile strength data of Examples 1-6 can be found in Figure 3 , the tensile strength data of Examples 7-12 are shown in Figure 4 .
[0104] from Figure 3It can be concluded that as the amount of filler increases, the tensile strength of the silane-modified polyether sealant increases from about 0.11MPa to about 1.0MPa, an increase of nearly 10 times, indicating that the filler plays a good reinforcing role. When the filler amount is 140 parts, the tensile strength of the silicone rubber reaches the maximum value, and the tensile strength shows a downward trend as the filler amount is further increased.
[0105] from Figure 4 It can be concluded that when the amount of cross-linking agent increases from 0.5 parts to 3.0 parts, the tensile strength of the sealant increases by about 2 times. This proves that the amount of coupling agent has a great influence on the mechanical properties of the sealant. The addition of coupling agent mainly has a great influence on the coupling density of the sealant. With the increase of the amount of coupling agent, the cross-linking density of the sealant increases. When subjected to external force, the number of network chains that can bear stress per unit area also increases, which increases the tensile strength of the sealant.
[0106] Test Example 4
[0107] In this test example, the low modulus silane-modified polyether sealant prepared in Examples 1-12 was tested for elongation at break. The test standard was to prepare the "dumbbell" type specimen according to GB / T528-2009 "Vulcanized rubber or thermoplastic rubber-Determination of tensile stress-strain properties", with a specification of 11.5×6×2mm and a thickness of 2mm. The specific preparation method is to fill the polytetrafluoroethylene mold with sealant, scrape the mold surface flat, and cure it under standard test conditions for 28 days, then take out the specimen, and the universal tensile test machine model of the tester is AI-7000S, and the tensile speed is 500mm / min. Among them, the elongation at break data of Examples 1-6 can be found in Figure 5 , the elongation at break data of Examples 7-12 are shown in Figure 6 .
[0108] from Figure 5 It can be concluded that the elongation at break also increases first and then decreases with the increase of filler content. When the filler content is 120 parts, the elongation at break of the prepared silane-modified polyether sealant reaches 1148%, which is almost 6 times that of the unfilled silane-modified polyether sealant. However, when the filler content is further increased to 160 parts, the elongation at break decreases greatly, from 1148% to 675%. From the data analysis of these mechanical properties, it can be seen that fillers have a significant reinforcing effect, and the change in content has an important influence on the reinforcing effect of fillers in silane-modified polyether sealants.
[0109] from Figure 6It can be concluded that with the increase in the amount of coupling agent, the elongation at break of the silane-modified polyether sealant first increases and then decreases, while the tensile strength gradually increases. This is mainly attributed to the fact that the terminal Si-OCH3 in the structure of the KH792 coupling agent can participate in the cross-linking and curing reaction of the sealant, thereby increasing the cross-linking density of the silane-modified polyether sealant.
[0110] Test Example 5
[0111] In this test example, the low modulus silane modified polyether sealant prepared in Examples 1-6 was tested for hardness. The test standard was GBT 531.2-2009 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber". The test instrument model was a Shore hardness tester. The sealant was made into a uniform film with a thickness of 2mm±0.2mm and placed under a standard environment for more than 7 days. During the test, three layers of the film were stacked. The test data of the hardness of Examples 1-6 can be found in Figure 7 .
[0112] from Figure 7 It can be concluded that as the amount of filler increases, the hardness of the obtained silane-modified polyether sealant increases. Therefore, the hardness of the sealant can be adjusted by adjusting the amount of filler added to guide actual use. For the three-dimensional network system of the sealant, the filler also acts as a cross-linking point. Therefore, an increase in the amount of filler is equivalent to increasing the active cross-linking points of the entire system, which increases the cross-linking density of the sealant, and ultimately leads to an increase in the hardness of the sealant as the amount of filler increases.
[0113] Test Example 6
[0114] This test example performs performance characterization tests on the low modulus silane-modified polyether sealants prepared in Example 7 and Example 13-14, wherein the test method for the surface drying time is GB / T13477.5-2017 "Test methods for building sealing materials Part 5: Determination of surface drying time", and the prepared sealant is filled into a standard mold with an internal size of 25mm×95mm, an external size of 50mm×120mm, and a thickness of 3mm. The test method for the curing rate is based on GB / T32369-2015 "Determination of the degree of curing of sealants", and the mold used for sample preparation is a wedge-shaped groove directly processed from a polytetrafluoroethylene plate. The test standards for tensile strength and elongation at break are the same as those described above. The relevant result data are shown in Table 1.
[0115] Table 1
[0116] Example 7 13 14 type KH792 KH560 KH550 Surface drying time / min 40 52 36 Curing rate / mm / 1d 2.65 2.47 2.78 Tensile strength / MPa 1.36 1.12 1.54 Elongation at break / % 560 423 545
[0117] As can be seen from Table 1, by comparing the surface drying time and curing time data of the sealants prepared by the three silane coupling agents, it can be seen that the sealant obtained by using KH550 as a coupling agent has the fastest curing rate and the shortest surface drying time; the sealant obtained by using KH560 as a coupling agent has the slowest curing rate and the longest surface drying time compared with the other two coupling agents; the sealant obtained by using KH792 as a coupling agent has a medium curing rate and surface drying time. By comparing the results of tensile strength and elongation at break, it can be found that the KH550 system has the highest tensile strength, while the elongation at break is at a medium level; on the contrary, the KH792 system shows the highest elongation at break, but its tensile strength is medium; in contrast, the KH560 system is lower than the other two systems in both tensile strength and elongation at break. This is because both coupling agents KH550 and KH792 have amino groups, which play a certain cross-linking role in the preparation process of sealants. Therefore, the tensile strength and elongation at break of the sealants prepared by the KH550 and KH792 systems are better than those of the KH560 system. Also, because the KH792 coupling agent contains diamino groups, and the KH550 coupling agent contains one amino group, the diamino coupling agent system can provide more cross-linking points for the sealant during the preparation process of the sealant, which can improve the performance of the MS sealant and also improve the elongation at break.
[0118] Test Example 7
[0119] In this test example, the performance characterization test of the low modulus silane-modified polyether sealant prepared in Examples 7-12 was conducted, wherein the surface drying time test method was the same as the above, and the damage relative area test method was GB / T13477.8-2017 "Test methods for building sealing materials Part 8: Determination of tensile adhesion" to conduct tensile adhesion test on the prepared sealant. The relevant result data are shown in Table 2.
[0120] Table 2
[0121]
[0122] As can be seen from Table 2, as the amount of coupling agent KH792 increases, the curing time of the sealant gradually increases. During the curing process, the coupling agent consumes a certain amount of water. If too much coupling agent is used, the water required for the sealant will be consumed, resulting in a longer surface drying time for the sealant. At the same time, the damaged surface of the sealant I-shaped specimen also changes from poor adhesion to cohesive failure as the coupling agent content increases. This is because the appropriate amount of coupling agent can increase the molecular force between the bonding interfaces and increase the cross-linking degree between silane-terminated polyether macromolecules, thereby improving the mechanical properties of the sealant and the adhesion to the substrate; but as the amount of coupling agent continues to increase, the cross-linking degree of the sealant will also decrease, resulting in a decrease in performance, which will also affect the bonding performance.
[0123] Test Example 8
[0124] This test example performs a performance characterization test on the low modulus silane-modified polyether sealant prepared in Example 7 and Examples 15-18, wherein the surface drying time test method is the same as that described above, and the relevant result data is shown in Figure 8 .
[0125] from Figure 8 It can be seen that when the addition ratio of plasticizers is the same, the surface drying time of the sealants obtained by DIDP and DOP is not much different, about 25 minutes; while the formulation with polypropylene glycol significantly prolongs the surface drying time, both exceeding 40 minutes. Compared with phthalate plasticizers, polypropylene glycol plasticizers have a longer surface drying time. This is because the hydroxyl groups in polypropylene glycol will consume the siloxy groups in the prepolymer. In the formulation using PPG as the plasticizer, when PPG1000 is the plasticizer, the surface drying time is up to 48 minutes. This is mainly because the -OH in PPG will react with the alkoxy group in the prepolymer, resulting in a longer surface drying time.
[0126] Test Example 9
[0127] This test example performs performance characterization tests on the low modulus silane-modified polyether sealants prepared in Example 7 and Examples 17-18, and the test standards for tensile strength and elongation at break are the same as those described above. The relevant result data are shown in Table 3.
[0128] Table 3
[0129] Example Plasticizer Type Tensile Strength Elongation at break 7 PPG3000 1.64 545 17 DIPN 1.28 480 18 DOP 1.15 465
[0130] As can be seen from Table 3, the mechanical properties of the sealant samples prepared using DIPN and DOP as plasticizers are similar, and DINP is relatively better. This is because DINP has a longer carbon chain than DOP and a larger relative molecular mass. DIPN is more resistant to aging and high temperature, and is more environmentally friendly.
[0131] The elongation at break of the sealant prepared using PPG3000 as a plasticizer is higher than that of the sealant prepared using DIPN and DOP. This is because a chain extension reaction can occur between polypropylene glycol and MS prepolymer, thereby extending the main chain of the MS prepolymer and improving its elongation at break while maintaining good mechanical properties. Adding PPG can increase the crosslinking density of the MS prepolymer, making the tensile strength better than the system with both DIPN and DOP plasticizers.
[0132] Test Example 10
[0133] In this test example, the low modulus silane-modified polyether sealant prepared in Example 7 and Examples 19-23 was subjected to performance characterization tests, wherein the surface drying time test method was the same as described above, and the extrusion test method was GBT13477.3-2017 "Test methods for building sealing materials Part 3 Method for determining the extrusion of sealing materials using standard instruments", and the relevant result data are shown in Table 4.
[0134] Table 4
[0135]
[0136] It can be seen from Table 4 that when the catalyst is dibutyltin dilaurate, as the catalyst dosage increases from 1 part to 2 parts, the surface drying time of the sealant is shortened from 60 minutes to 25 minutes, but the viscosity of the sealant increases slightly. When the catalyst is dibutyltin diacetate, as the catalyst dosage increases from 1 part to 2 parts, the surface drying time of the sealant is shortened from 75 minutes to 45 minutes, but the viscosity of the sealant thickens significantly.
[0137] In summary, the low modulus silane-modified polyether sealant provided by the present invention is based on the perspective of filler, and foamed ceramic tailings are added as fillers during the preparation process for recycling. The preparation method contains huge economic potential and can also save a large amount of natural resources. By changing the performance of the filler, the purpose of reducing costs and strengthening toughness is achieved. Through the reasonable regulation of plasticizers, coupling agents, and catalysts, and the ratio setting between the raw materials, the elongation at break of the prepared low modulus silane-modified polyether sealant is 1148% (filler content is 120 parts), showing good flexibility. The preparation method is simple and easy to operate. The prepared present invention recycles the foamed ceramic tailings, which helps to protect the ecological environment while reducing cost investment. It can be widely promoted in the field of prefabricated buildings and improve people's quality of life.
[0138] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low modulus silane-modified polyether sealant, characterized in that: The low modulus silane-modified polyether sealant comprises the following raw materials in parts by mass: 50-100 parts of silane-modified polyether polymer, 30-50 parts of plasticizer, 30-180 parts of filler, 1-4 parts of coupling agent, 1-2 parts of catalyst; The filler is foamed ceramic tailings.
2. The low modulus silane-modified polyether sealant according to claim 1, characterized in that: The silane-modified polyether polymer is selected from any one of trimethoxysiloxane-terminated polyether and dimethoxysiloxane-terminated polyether.
3. The low modulus silane-modified polyether sealant according to claim 1, characterized in that: The filler is 80-180 parts by mass.
4. The low modulus silane-modified polyether sealant according to claim 1, characterized in that: The plasticizer is selected from any one of polypropylene glycol, polybutylene glycol, diethyl phthalate, dioctyl phthalate and bisphenol A epoxy resin.
5. The low modulus silane-modified polyether sealant according to claim 1, characterized in that: The coupling agent is selected from any one of 3-(aminopropyl)trimethoxysilane, N-2-(aminoethyl)-3-(aminopropyl)trimethoxysilane, 3-(aminopropyl)triethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
6. The low modulus silane-modified polyether sealant according to claim 5, characterized in that: The coupling agent includes N-2-(aminoethyl)-3-(aminopropyl)trimethoxysilane.
7. The low modulus silane-modified polyether sealant according to claim 1, characterized in that: The catalyst is selected from any one of dibutyltin dilaurate and dibutyltin diacetate; Preferably, the catalyst is dibutyltin dilaurate.
8. A method for preparing the low modulus silane-modified polyether sealant according to any one of claims 1 to 7, characterized in that: The preparation of the low modulus silane-modified polyether sealant comprises the following steps: The silane-modified polyether polymer, the plasticizer and the filler are reacted in proportion, the reaction temperature is 60-120° C., the reaction time is greater than 0.5 h, and the vacuum degree is greater than or equal to -0.09 MPa to obtain a first mixed material; After the first mixed material is cooled to 25-45° C., it is reacted with a coupling agent and a catalyst, the reaction time is ≥0.5h, the vacuum degree is ≥-0.09MPa, and it is cooled to room temperature to obtain the low modulus silane-modified polyether sealant.
9. The preparation method according to claim 8, characterized in that: The filler also includes: The foamed ceramic tailings, balls and water are added into a ball mill for ball milling in a mass ratio of (1.0-1.5):(1.6-2.7):(0.6-0.8), and the slurry after ball milling is dried to obtain the filler.
10. Use of the low modulus silane-modified polyether sealant as claimed in any one of claims 1 to 7 or the low modulus silane-modified polyether sealant prepared by the preparation method as claimed in any one of claims 8 to 9 in the field of prefabricated buildings.
